INCREASING THE METHANE OUTPUT BY ADDING THE ACTIVATED CARBON FOR THE PRODUCTION OF BIOGAS - Marat SATAYEV; Zhanar KAIPOVA; Aigul JANMULDAEVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Research has shown that activated carbon can increase the production of biogas and methane from anaerobic digestion, thereby reducing the startup time. Activated carbon has raised the possibility of microbial resistance to the organic load. A more developed structure of mesoporous the activated carbon was favorable for the colonization of specific bacteria, which leads to increased syntrophic associations between bacteria and methane producers. Thus, the anaerobic reactor complemented with activated carbon would be economically efficient for the production of biogas.